MOBILE COMMERCE READINESS AMONG MALAYSIAN YOUTH - K. Sugathan , Savita; Chen , Yoke Yie; Patah Akhir, Emelia Akashah; Emy Elyanee , Mustapha; Mehat , Mazlina (2009)
Mobile commerce (m-commerce) is any transaction that can be conducted using a mobile device. In Malaysia, m-commerce is still in its early stage of development. While there has been a great deal of excitement in view of m-commerce implementing in Malaysia, little do we know how well the youth in Malaysia is ready to adopt this technology. This paper presents an analysis of m-commerce readiness among youth in Malaysia by looking at how youth response to the m-commerce service that is available and the factors that may affect the adoption of m-commerce among youth. A quantitative research method was used to carry out the survey. The study found out that the youth are ready to use m-commerce services but there are two barriers that could affect their readiness level which are: their allowance or pocket money they receive every month and the availability of m-commerce service in the country itself.